Transformation Strategy of Omni-Channel Marketing (OCM) Based on Digital Innovation to Foster Sustainable Competitive Advantage for MSMEs - Lazuardi, Dedy; Ihdina Gustina; Nurmala Sridewi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Micro, Small, and Medium Enterprises (MSMEs) still rely on conventional marketing strategies that are less effective in enhancing competitiveness. According to data from the Ministry of Cooperatives and SMEs (KemenKopUKM), only 21% of MSMEs have adopted digital approaches, with remaining challenges including limited infrastructure, lack of digital skills, and minimal policy support. Omni-Channel Marketing (OCM) based on digital innovation emerges as a strategic solution to expand market reach, improve business efficiency, and create sustainable competitive advantage. In line with the President's Asta Cita Point 3, "promoting entrepreneurship," a transformative strategy for OCM driven by digital innovation is needed to help MSMEs survive and grow in an increasingly competitive global market. This study employs a quantitative approach. The sample consists of 1,000 MSMEs in Medan City, selected using purposive sampling. Data were collected through a questionnaire survey. The study uses Partial Least Squares (PLS) with SmartPLS software for data analysis. The findings indicate that the Omni-Channel Marketing (OCM) Transformation Strategy and Digital Innovation have a positive and significant effect on Sustainable Competitive Advantage. Moreover, the OCM Transformation Strategy influences Digital Innovation, and the OCM Transformation Strategy, mediated by Digital Innovation, also affects Sustainable Competitive Advantage.